Analisis Kualitas Kehidupan Kerja Dan Kinerja Guru - Eka Askafi (Otonomi, 2023)
Educators are expected to have a significant influence on the formation of human resources in the cognitive, affective and skills, both in terms of physical, mental and spiritual. This obviously requires a good quality of education as well as professional educators, so the quality of education can be truly optimal role in people's lives. For that educators are required to always improve, to develop themselves in the education building. The objective of this study is to examine the effect of quality of worklife, and teachers performance, also testing the effect of quality of worklife on teachers performance at Islamic High School in Jombang.The sampling technique in this study using Proportionate Random Sampling. These results indicate that good quality of work life it can encourege teachers to good performance